Ewolucja podatku od spadków i darowizn z punktu widzenia celów ekonomicznych - Czerniec, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
The article describes economic role of donation and inheritance taxes. In the first part of the article the author presents evolution of these taxes, from ancient times to present, and also considers functioning of these taxes in Poland from times of the First Republic of Poland. The role of these taxes in Poland from the 90’s to present is thoroughly analysed. In conclusion the author states that donation and inheritance taxes do not play the fundamental role in realization of economic aims and do not have a significant influence on economic development.
Keywords: podatek od spadków i darowizn